Hands up - let's Sign : a teacher's guide on Sign Language courses for families. (Athene : Hellenic Federation of the Deaf - O.M.K.E., 2001)
Instructievideo voor leerkrachten gebarentaal, over hoe je moet lesgeven in de familiale context.